The Resurgam submarine : 'a project for annoying the enemy' - Holt, Peter (Engineer), (Archaeopress archaeology., 2017)
The Resurgam is one of the earliest 'working' submarines, designed by Victorian engineer George William Garrett. This text describes how the Resurgam was built, how she may have worked and what happened to her.